Impact of Primary Immunodeficiency Diseases on the Life Experiences of Patients in Malaysia From the Caregivers' Perspective: A Qualitative Study - Ruwaydah Ahmed Meelad; Intan Juliana Abd Hamid; Ilie Fadzilah Hashim; Zarina Thasneem Zainudeen; Firdaus Farhani Abu Bakar; Fahisham Taib; Norsarwany Mohamad; Ernest Mangantig; Intan Hakimah Ismail; Amir Hamzah Abdul Latiff; Lokman Mohd Noh (Frontiers Media S.A., 2022)
IntroductionPrimary immunodeficiency diseases (PIDs) are chronic diseases that affect the various aspects of a patient's life. However, the impact of living with PIDs is poorly described.ObjectiveThis study aimed to explore the living experience challenges among the Malaysian caregivers of the patients with PID who underwent a follow-up in the Universiti Sains Malaysia or those registered members of the Malaysian PIDs Society.MethodologyThe study was conducted from March 1 to May 30, 2021. The parents of children with PIDs were invited to participate for a semi-structured in-depth interview at the PID clinics in the USM. The estimated time of each interview was 30 min. The semi-structured interview was performed via a telephone call because of COVID-19 pandemic restrictions. The audio recording of each interview was transcribed and translated from Malay to English. Subsequently, a thematic analysis utilizing the ATLAS.ti software was performed.ResultsThe thematic analysis revealed five main themes, which are living with fear and anxiety with four sub-themes (sickness, psychological issues, fear of infections and hereditary issues), PID healthcare support struggles with four sub-themes (PID health system, treatment, diagnosis and financial issues), knowledge with two sub-themes (educational issues and disease understanding), social constraint with two sub-themes (relationships and social isolations) and coping with three sub-themes (acceptance, child health improvement and emotional hygiene).ConclusionLiving with fear and anxiety is a major theme impacting the living experiences of Malaysian patients with PIDs. Improvements in healthcare delivery and disease education are needed to ensure optimal quality of life.